1988
DOI: 10.1111/j.1439-0450.1988.tb00554.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Neutrophil Function in the Dairy Cow during the Perinatal Period

Abstract: Chernotactic response, luminol dependent chemilurninescence of neutrophils and cortisol concentration in blood plasma were measured in 10 dairy cows in order to evaluate neutrophil function during the perinatal period. A decrease in chemotactic response was observed in correlation with parturition. This reduction may be due to the high concentration accompanying parturition and stress during this period. The results indicate a decrease in neutrophil function. The increased susceptibility to bacterial infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…We think that this reduction in L-selectin receptors can have a negative impact on the ability of PMN to be recruited into the mammary gland. Random migration and chemotaxis are impaired during the first week after calving [2,28], as are phagocytosis [16,21,34] and respiratory burst activity [12,19,21]. A recent study reported a significant drop in L-selectin expression between 9 and 24 h after calving [25].…”
Section: Discussionmentioning
confidence: 99%
“…We think that this reduction in L-selectin receptors can have a negative impact on the ability of PMN to be recruited into the mammary gland. Random migration and chemotaxis are impaired during the first week after calving [2,28], as are phagocytosis [16,21,34] and respiratory burst activity [12,19,21]. A recent study reported a significant drop in L-selectin expression between 9 and 24 h after calving [25].…”
Section: Discussionmentioning
confidence: 99%
“…Briefty, Guidry et al (1976) first reported a reduced phagocytic capacify of neutrophils during the peripartum period. A decade later, research ftarther indicated that neutrophil chemotaxis, Superoxide anión production, and total killing capacify were also attenuated during the peripartum period (Nagahata et al, 1988;Kehrli et al, 1989). A more direct causal link between neutrophil ftinction and the severify of E. coli mastitis was observed in the data from Heyneman et al (1990), who reported a greater incidence of serum-resistant E. coli mastitis in cows that had a decreased neutrophil oxidative burst capacify.…”
Section: Clinical Diseasementioning
confidence: 96%
“…The function of neutrophils in host defense mechanisms relies heavily on phagocytosis. Previous studies [20,33,34] showed that polymorphonuclear cell (PMN) function was impaired in the cow during the peripartum period, which suggested that attenuated PMN function contributed to the increased incidence of postpartum diseases. We found that for both the endometritis and control cow groups, the phagocytic capacity of their leukocytes increased at calving relative to the week 1 prepartum capacity, and that this then dropped within a week to the start values; these levels were then maintained for the remainder of the study.…”
Section: Discussionmentioning
confidence: 99%